Morbidity and mortality outcomes of COVID-19 patients with and without hypertension in Lagos, Nigeria: a retrospective cohort study - Akin Abayomi; Akin Osibogun; Oluchi Kanma-Okafor; Jide Idris; Abimbola Bowale; Ololade Wright; Bisola Adebayo; Mobolanle Balogun; Segun Ogboye; Remi Adeseun; Ismael Abdus-Salam; Bamidele Mutiu; et al. (BMC, 2021)
Abstract Background The current pandemic of coronavirus disease (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has shown epidemiological and clinical characteristics that appear worsened in hypertensive patients. The morbidity and mortality of the disease among hypertensive patients in Africa have yet to be well described. Methods In this retrospective cohort study all confirmed COVID-19 adult patients (≥18 years of age) in Lagos between February 27 to July 62,020 were included. Demographic, clinical and outcome data were extracted from electronic medical records of patients admitted at the COVID-19 isolation centers in Lagos. Outcomes included dying, being discharged after recovery or being evacuated/transferred. Descriptive statistics considered proportions, means and medians. The Chi-square and Fisher's exact tests were used in determining associations between variables. Kaplan-Meier survival analysis and Cox regression were performed to quantify the risk of worse outcomes among hypertensives with COVID-19 and adjust for confounders. P-value ≤0.05 was considered statistically significant. Results A total of 2075 adults with COVID-19 were included in this study. The prevalence of hypertension, the most common comorbidity, was 17.8% followed by diabetes (7.2%) and asthma (2.0%). Overall mortality was 4.2% while mortality among the hypertensives was 13.7%. Severe symptoms and mortality were significantly higher among the hypertensives and survival rates were significantly lowered by the presence of additional comorbidity to 50% from 91% for those with hypertension alone and from 98% for all other patients (P < 0.001). After adjustment for confounders (age and sex), severe COVID-19and death were higher for hypertensives {severe/critical illness: HR = 2.41, P = 0.001, 95%CI = 1.4-4.0, death: HR = 2.30, P = 0.001, 95%CI = 1.2-4.6, for those with hypertension only} {severe/critical illness: HR = 3.76, P = 0.001, 95%CI = 2.1-6.4, death: crude HR = 6.63, P = 0.001, 95%CI = 3.4-1.6, for those with additional comorbidities}. Hypertension posed an increased risk of severe morbidity (approx. 4-fold) and death (approx. 7-fold) from COVID-19 in the presence of multiple comorbidities. Conclusion The potential morbidity and mortality risks of hypertension especially with other comorbidities in COVID-19 could help direct efforts towards prevention and prognostication. This provides the rationale for improving preventive caution for people with hypertension and other comorbidities and prioritizing them for future antiviral interventions.